HEATING AND COOLING SYSTEM - KRUMHANSL, MARK URBAN (1982)
Heating and cooling of dwelling houses and other confined spaces is facilitated by a system in which thermal energy is transported between an air heating and cooling system in the dwelling and a water heat storage sink or source, preferably in the form of a swimming pool or swimming pool and spa combination. Special reversing valve circuitry and the use of solar collectors and liquid-to-liquid heat exchangers on the liquid side of the system, and special air valves and air modules on the air side of the system, enhance the system's efficiency and make it practical in the sense that systems employing the invention can utilize existing craft skills and building financing arrangements and building codes, and the like, without major modification.